Implementasi Dinamic Programing Untuk Menentukan Program Diet Bagi Penderita Kegemukan (Obesitas) - Khairullah, Khairullah; Lala, Andi (UNIVED Press, 2019)
In the past, people tended to be more active, because to carry out an activity a lot of physical activity was needed. Nowadays, people are too lazy to change the TV channel, so it is not surprising that obesity, high blood pressure and heart disease have become epidemics affecting public health. The increasing trend of weight loss recently has also been accompanied by an increase in the production of drugs and food substitutes which are promoted as slimming foods that are healthy and highly nutritious, even though we may know that these products generally only help suppress hunger for a while. If the body needs to consume daily food that contains balanced nutrients, if the body can digest, absorb and metabolize these nutrients properly, an ideal body weight and balanced nutritional condition will be achieved. So it can be concluded that SPK software is needed that can provide information on diet analysis, planning food menus and sports activity schedules quickly and accurately. To solve the problem of preparing diet programs for obese sufferers, a linear programming model with a dynamic programming method was chosen, because the application of the programming method linear on this problem can provide information on planning a food menu with nutritional content that will not exceed the limited number of nutrients.